ChemInform Abstract: Crystal Structure and Morphology Control of Molybdenum Carbide Nanomaterials Synthesized from an Amine—Metal Oxide Composite. Issue 4 (28th January 2014) - Wan, Cheng; Knight, Nicole A.; Leonard, Brian M.
Abstract Molybdenum carbide nanomaterials are synthesized by thermal decomposition (625—900 °C) of precipitates obtained from mixtures of (NH4)6Mo7O24 and an amine in water (pH <3 adjusted with HCl, 50 °C, 2.5 h).